Síntese, Caracterização e Avaliação Antimicrobiana de Novos Derivados do Sistema 1,3,4-oxadiazol - Santos, Alexsandro Fernandes dos (2015)
Two series based on the structure of 2,5-diaryl-1,3,4-oxadiazole were synthesized, 2-aryl-5-methyl-1,3,4-oxadiazole (1a,h) and 2-aryl-5- trifluoromethyl-1,3,4-oxadiazole (2a,e), and their biological activity were investigated. These compounds had their chemical structures characterized with spectrometric methods such as IR, 1H and 13C NMR. To characterize the compound 2-(2-acetoxyphenyl)-5-methyl-1,3,4- oxadiazole, it was necessary the use of two-dimensional NMR techniques (COSY, HMQC and HMBC) and his structural arrangement was analyzed by the crystallographic X-ray technique. Mass spectrometric investigation, unprecedented for this class of compound, was also performed. All compounds were tested against eight strains of Staphylococcus aureus, Escherichia coli and also against strains of Aspegilles fumigatus, Aspegilles flavus, Candida albicans, Candida albicans and Candida tropicalis. The results showed that compounds 1b, 1c, 1e, 1g, 2a and 2c, produced inhibition on the growth of species of bacteria and fungi, where the MIC was set between 512 to 1224 mg mL-1. While the compounds 1d, 1e, 1f, 1h, 2a and 2b were inactive, the compounds 1d, 1e, 1f, 1h, 2a and 2b reported a broad spectrum.